2013
DOI: 10.1111/acem.12229
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Ketamine for Analgesia in the Emergency Department: A Prospective Observational Series

Abstract: Objectives: The objective was to examine the feasibility, effectiveness, and adverse effect profile of intranasal ketamine for analgesia in emergency department (ED) patients.Methods: This was a prospective observational study examining a convenience sample of patients aged older than 6 years experiencing moderate or severe pain, defined as a visual analog scale (VAS) score of 50 mm or greater. Patients received 0.5 to 0.75 mg/kg intranasal ketamine. Pain scores were recorded on a standard 100-mm VAS by traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
2
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 11 publications
(11 reference statements)
1
77
2
2
Order By: Relevance
“…[ [5][6][7] The patients received a single dose of 0.3 mg/kg or an additional dose of IN ketamine if the VAS remained 50 mm or higher at 15 minutes after the initial administration of the agent. Dosing was calculated previously for 0.7 mg/kg and 0.3 mg/kg and doses were rounded in the table in five kg weight bands for ease of dose and volume calculation so as to reduce risk of dosing error.…”
Section: Study Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…[ [5][6][7] The patients received a single dose of 0.3 mg/kg or an additional dose of IN ketamine if the VAS remained 50 mm or higher at 15 minutes after the initial administration of the agent. Dosing was calculated previously for 0.7 mg/kg and 0.3 mg/kg and doses were rounded in the table in five kg weight bands for ease of dose and volume calculation so as to reduce risk of dosing error.…”
Section: Study Proceduresmentioning
confidence: 99%
“…[4] Because of this analgesic effect at a low dose, patients often remain completely awake and alert and no deleterious or clinically signifi cant hemodynamic or respiratory effects were noted previously, therefore close physiological monitoring of the patients can be avoided in contrast to opioids. [2,[4][5][6][7] IN ketamine in the ED has been explored in recent years internationally; [5][6][7] however, the results are controversial. Recent studies [5,6] have demonstrated adequate analgesia with IN ketamine, whereas one study [7] concluded that IN ketamine had a relatively low response rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Andolfatto G, et al [15] used Intranasal ketamine for analgesia in the emergency department in a study and have reached a conclusion that intranasal ketamine lowered VAS pain scores to a clinically significant degree in 88% of emergency department (ED) patients Also Roshana S, et al [16] tried intranasal ketamine for the treatment of patients with acute pain in the ED and concluded that intranasal ketamine is an analgesic choice for acute injury patients with moderate to severe pain especially in an overcrowded and resource limited ED.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasal fentanyl has been widely reported to be an effective tool in pediatric pain relief along with other opiates (4). However, ketamine has only recently been described for the provision of analgesia in pediatric emergency settings (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%